Soft computing systems : second International Conference, ICSCS 2018, Kollam, India, April 19-20, 2018, revised selected papers /: second International Conference, ICSCS 2018, Kollam, India, April 19-20, 2018, revised selected papers. (2018) - Unknown
No abstract available